Association between lncRNA GAS5, MEG3, and PCAT-1 Polymorphisms and Cancer Risk: A Meta-Analysis. (28th March 2020) - Dong, Xiaoyan; Gao, Wenyan; LV, Xiaoling; Wang, Yazhen; Wu, Qing; Yang, Zhouxin; Mao, Genxiang; Xing, Wenmin
Abstract : Purpose . Long noncoding RNAs (lncRNAs) have been widely studied, and single nucleotide polymorphisms (SNPs) in lncRNAs are considered to be genetic factors that influence cancer susceptibility. The lncRNA GAS5, MEG3, and PCAT-1 polymorphisms are shown to be possibly associated with cancer risk. The aim of this meta-analysis was to systematically evaluate this association. Methods . Studies were selected from PubMed, Web of Science, Embase, Google Scholar, Cochrane Library, the Chinese National Knowledge Infrastructure (CNKI), and the Chinese Biomedical Literature Database (CBM) through inclusion and exclusion criteria. Odds ratios (ORs) and 95% confidence intervals (CIs) were calculated using the random-effects model or fixed-effects model to assess the association between lncRNA polymorphisms and cancer susceptibility. Metaregression and publication bias analyses were also conducted. All analyses were performed using the Stata 12.0 software. Results . Sixteen articles (covering 13750 cases and 17194 controls) were included in this meta-analysis. A significant association between SNP rs145204276 and gastric cancer risk was observed ( del vs. ins : OR = 0.79, 95 % CI = 0.72 ‐ 0.86 ; del/del vs. ins/ins+del/ins : OR = 0.74, 95 % CI = 0.59 ‐ 0.91 ; del/ins vs. ins/ins : OR = 0.84, 95 % CI = 0.67 ‐ 1.05 ). For rs16901904, a decreased cancer risk was observed in three genetic models ( C vs. T : OR = 0.79, 95 % CI = 0.70 ‐ 0.90 ; CC vs. CT+TT : OR = 0.49, 95 % CI = 0.37 ‐ 0.65 ; CC vs. TT : OR = 0.49, 95 % CI = 0.37 ‐ 0.66 ). No statistical significance was found in the metaregression analysis. For all of the included SNPs, no publication bias was found in all genotype models. Conclusions . The rs145204276 SNP in lncRNA GAS5 is likely to be associated with gastric cancer risk, whereas the rs16901904 SNP in lncRNA PCAT-1 bears association with a decreased cancer risk.